2011
DOI: 10.1007/s10875-011-9625-4
|View full text |Cite
|
Sign up to set email alerts
|

Increased Pro-inflammatory Cytokine Production in Down syndrome Children Upon Stimulation with Live Influenza A Virus

Abstract: Children with DS have an altered immune response to influenza A virus. The production of higher levels of pro-inflammatory cytokines may be responsible for a more severe clinical course of viral disease in these children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 39 publications
2
32
0
3
Order By: Relevance
“…Also, an increased risk of hospitalization, endotracheal intubation, and death due to influenza A virus infection was reported in DS (29). In addition, we found an increased proinflammatory cytokine response to live influenza A virus in children with DS, which might contribute to an increased severity of their clinical course of this infection (30). Bacterial pathogens, both Gram positive and Gram negative, can also cause lower RTIs in children.…”
supporting
confidence: 52%
“…Also, an increased risk of hospitalization, endotracheal intubation, and death due to influenza A virus infection was reported in DS (29). In addition, we found an increased proinflammatory cytokine response to live influenza A virus in children with DS, which might contribute to an increased severity of their clinical course of this infection (30). Bacterial pathogens, both Gram positive and Gram negative, can also cause lower RTIs in children.…”
supporting
confidence: 52%
“…It can be responsible for increased incidence of infections, mainly in the respiratory tract (Bloemers et al, 2010;Broers et al, 2012), and occurrence of autoimmune disease in DS (Gillespie et al, 2006;Pellegrini et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The cytokines belong to a diversified group of protein, which participated in various biological processes, including the mediation of the inflammatory response (Zhang and An, 2007). Changes in the concentration of proinflammatory and anti-inflammatory cytokines in DS individuals demonstrate its association with the syndrome pathogenesis (Tsilingaridis et al, 2003;Guazzarotti et al, 2009;Cetiner et al, 2010;Broers et al, 2012Broers et al, , 2014. The study of Cetiner et al (2010) observed that the IL6 serum levels were lower in DS children compared with individuals without the syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Например, у мышей линии DBA, продуцирую-щих в ответ на гриппозную инфекцию высокие уров-ни IFN I типа, летальная инфекция развивается при заражении дозами, безопасными для мышей линии С57BL/6 с умеренной выработкой IFN [83,84]. У людей с синдромом Дауна выявлена повышен-ная чувствительность к респираторным инфекциям и высокая вероятность тяжелых осложнений, сопря-жённых с генетически обусловленной гиперпродук-цией IFN α/γ в ответ на вирусную инфекцию [85].…”
Section: роль интерферонового ответа в патогенезе вторичных бактериалunclassified